Expression of β-catenin, Ki67 and stroma percentage in colorectal cancer - Suanno, Cristina (2021)
AIMS. The purpose of this study was to explore the expression of β-catenin, Ki67 and stroma percentage in colorectal cancer and investigate their role as biological and prognostic biomarkers.